Elucidation of the Signatures of Proteasome-Catalyzed Peptide Splicing - Paes, Wayne; Leonov, German; Partridge, Thomas; Nicastri, Annalisa; Ternette, Nicola; Borrow, Persephone (Frontiers in Immunology, 2020)
Proteasomes catalyse the degradation of endogenous proteins into oligopeptides, but can concurrently create spliced oligopeptides through ligation of previously non-contiguous peptide fragments. Recent studies have uncovered a formerly unappreciated role for proteasome-catalysed peptide splicing (PCPS) in the generation of non-genomically templated human leukocyte antigen class I (HLA-I)-bound cis-spliced peptides that can be targeted by CD8+ T cells in cancer and infection. However, the mechanisms defining PCPS reactions are poorly understood. Here, we experimentally define the biochemical constraints of proteasome-catalysed cis-splicing reactions by examination of in vitro proteasomal digests of a panel of viral- and self-derived polypeptide substrates using a tailored mass-spectrometry-based de novo sequencing workflow. We show that forward and reverse PCPS reactions display unique splicing signatures, defined by preferential fusion of distinct amino acid residues with stringent peptide length distributions, suggesting sequence- and size-dependent accessibility of splice reactants for proteasomal substrate binding pockets. Our data provide the basis for a more informed mechanistic understanding of PCPS that will facilitate future prediction of spliced peptides from protein sequences.